Tolerogenic signals delivered by dendritic cells to T cells through a galectin-1-driven immunoregulatory circuit involving interleukin 27 and interleukin 10 - Ilarregui, Juan Martin (2009)
Despite their central function in orchestrating immunity, dendritic cells (DCs) can respond to inhibitory signals by becoming tolerogenic. Here we show that galectin-1, an endogenous glycan-binding protein, can endow DCs with tolerogenic potential. After exposure to galectin-1, DCs acquired an interleukin 27 (IL-27)-dependent regulatory function, promoted IL-10-mediated T cell tolerance and suppressed autoimmune neuroinflammation. Consistent with its regulatory function, galectin-1 had its highest expression on DCs exposed to tolerogenic stimuli and was most abundant from the peak through the resolution of autoimmune pathology. DCs lacking galectin-1 had greater immunogenic potential and an impaired ability to halt inflammatory disease. Our findings identify a tolerogenic circuit linking galectin-1 signaling, IL-27-producing DCs and IL-10-secreting T cells, which has broad therapeutic implications in immunopathology.